A review on poly lactic acid (PLA) as a biodegradable polyme - Nur Azzah Afifah, Taib; Md Rezaur, Rahman; Durul, Huda; Kuok King, Kuok; Sinin, Hamdan; Muhammad Khusairy, Bakri; Muhammad Rafiq Mirza, Julaihi; Afrasyab, Khan (Springer Nature, 2023)
Biodegradable plastics are among the most promising materials to replace conventional petroleum-based plastics that have caused many adverse impacts on the environment, such as pollution (land, water, etc.) and global warming. Among a range of biodegradable plastics, poly lactic acid (PLA) is not only widely available but also safe to be decomposed after its usage without polluting the environment. PLA is also in parity with other conventional plastics such as PP, PET in terms of various properties suitable for industrial usage such as mechanical, physical, biocompatibility and processability. Thus, PLA has become the most used biopolymers in many industries such as agriculture, automotive and packaging by having these characteristics. Its higher demand has contributed to a stable increment in the global PLA market. In fact, over the years, the market for PLA has grown up and will keep on expanding in the future. Overall, the PLA-based bioplastic would be an excellent substitute for the existing conventional plastics in various applications, hence will serve to protect the environment not only from pollution but also work as a sustainable and economical product. This paper will review all the recent related works and literature on PLA as the biodegradable material regarding its properties, usability, productivity and substitute.